Multiattribute evaluation - Edwards, Ward, 1927-2005. (Quantitative applications in the social sciences ;, 1982)
This book presents one approach to evaluation, multiattribute utility technology, which stresses that evaluations should be comparative, and that all the different constituencies served by a programme and its different goals have to be kept in mind.